2017
DOI: 10.1155/2017/4898914
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Personalized Bowel Preparation Using a Smartphone Camera Application: A Randomized Pilot Study

Abstract: Background We aimed to investigate the effectiveness of a smartphone application that analyzes and judges the optimal dosage of polyethylene glycol (PEG) for bowel preparation. Methods Patients were assigned to use the smartphone camera application (app group) or written instructions (non-app group). The smartphone camera application was programmed to analyze the bowel preparation quality and automatically determine the dosage of PEG from an analysis of stool images. In contrast, the non-app group consumed PEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Half (50%) the studies were conducted in South Korea [ 29 31 , 33 , 35 ], 2 in China [ 32 , 38 ], and one each in Lebanon [ 36 ], Spain [ 34 ], and Germany [ 37 ]. Studies took place in university hospitals [ 31 , 35 , 36 , 38 ], health examination clinics [ 30 ], tertiary-care hospitals [ 33 , 37 ], and hospital outpatient colonoscopy clinics [ 29 , 32 , 34 ]. Participants ranged in age from 18 to 80 years, with average age ranging from 44.4 to 57.6 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Half (50%) the studies were conducted in South Korea [ 29 31 , 33 , 35 ], 2 in China [ 32 , 38 ], and one each in Lebanon [ 36 ], Spain [ 34 ], and Germany [ 37 ]. Studies took place in university hospitals [ 31 , 35 , 36 , 38 ], health examination clinics [ 30 ], tertiary-care hospitals [ 33 , 37 ], and hospital outpatient colonoscopy clinics [ 29 , 32 , 34 ]. Participants ranged in age from 18 to 80 years, with average age ranging from 44.4 to 57.6 years.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the mHealth interventions are presented in Table 2 . MHealth interventions included smartphone apps [ 34 , 36 ], SMS text messages [ 33 , 35 , 37 , 38 ], smartphone camera app [ 31 ], smartphone video clips [ 29 , 30 ], and a social media app (WeChat) [ 32 , 38 ]. Operating platforms were Android only, iOS only, or both.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if clinicians use many methods to improve intestinal cleanliness, such as WeChat, SMS, phone reminder, and laxatives, the intestinal cleanliness is improved to some extent [10][11][12][13][14][15]. Because intestinal cleanliness is the foundation of ADR, even the best new foundation must be achieved with good intestinal cleanliness [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…To maintain an appropriate preparation-to-colonoscopy interval, the patient can be informed of the time of the last intake of the preparation agent via short message service [10], according to the scheduled time of colonoscopy. Further, a method of evaluating bowel cleansing using a smartphone application has been introduced to reduce the dosage of the bowel preparation agent [11]. In this issue of Clinical Endoscopy , Jeon et al [12] reported the usage of smartphone mobile messenger to help bowel preparation before colonoscopy.…”
mentioning
confidence: 99%